Constructing Criterion Referenced Tests in Mathematics for The Basic grades (5th. to 10th.) and investigating their Psychometric Properties - Batsh, Mohammad; Tarawneh, Ekhleif; Awwad, Ferial; Omari, Hamzah (DIRASAT: EDUCATIONAL SCIENCES, 2019)
This study aims at constructing criterion referenced tests in mathematics for the grades (5th. to 10th.) and investigating their psychometric properties, all the mathematical domains and the related intended learning outcomes (ILO's) are identified, the items that best measure these domains and ILO's are constructed, edited, and included in specially prepared templates. The necessary instructions for the administration of the tests are also included in the tests booklets. The population consists of (837471) students from the different grades. The tests are applied on a sample consisting of 3301 students from the six grades.The cut-off scores used to distinguish mastering students from non-mastering students in math are determined using Angoff method and contrast groups. The validity of the tests is established using content validity, decision validity, and criterion referenced validity/ concurrent. Reliability is established using Cronbach alpha, Livingstone method, Carver coefficient and Kappa coefficient. The results indicate sufficient indicators for psychometric properties of items and tests.